Effect of banana leaf pruning on legume yield in bananalegume intercropping systems in Eastern Democratic Republic of Congo - Ntamwira, J.; Pypers, Pieter; Asten, Piet J.A. van; Vanlauwe, Bernard; Ruhigwa, B.; Lepoint, P.C.E.; Blomme, Guy (Elsevier, 2013)
As a result of declining farm/plot size and increasing food security needs, intercropping is practised by the majority of small-scale farmers in eastern Democratic Republic of Congo. A banana-legume intercropping experiment was conducted at the Mulungu Research Station in South Kivu Province to evaluate whether banana leaf pruning improves legume biomass and grain yield without reducing banana production. Treatments consisted of combinations of three different levels of banana leaf pruning (maintain four or seven functional leaves, or all leaves) with three bio-fortified leguminous crops (bush bean, climbing bean and soybean). Plots with sole banana or leguminous crops were also included, resulting in a full factorial design with 15 treatments. The banana genotype was an East African highland cooking banana 'Barhabesha' (Musa spp., AAA-EA). The legume crops were planted in the established banana fields and observations were taken during two consecutive cropping seasons. Few significant differences were observed in legume biomass or grain yield between the four- and seven-banana leaf treatments for bush beans during both cropping seasons. However, with climbing beans, and especially soybeans, a significant difference was observed in biomass and grain yield between the four- and sevenleaf treatments during the second cropping season, when a more mature banana leaf canopy had developed. We recommend keeping seven green leaves on a banana plant when cultivating bush beans, as this treatment will improve light penetration but may not significantly affect banana growth and yield. In contrast, for climbing beans and especially soybeans, a more severe banana leaf pruning treatment is needed to obtain a reasonable legume biomass and grain yield. Banana landraces or hybrids with more erect leaves could also be envisaged for intercropping purposes, as they will create less shade for the legume crop, although rigorous de-suckering will need to be practised. Alternatively, cultivars with a regulated suckering (i.e. only two to three suckers develop) could be envisaged.